Optical Code Division Multiple Access (OCDMA) using Double Weight (DW) Codes for local area network - Dayang Khadijah, Hamzah; Syed Alwee Aljunid, Syed Junid, Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/